Rintangan Bisnis Digital - Surahman, Piqih Adi; Hidayat, Arvando Nanda; Saputra, Muhammad Ihsan Sajid (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to identify and analyze the various challenges faced by businesses in adopting and developing operations in the digital era. Despite presenting complex challenges, digital transformation has opened many opportunities for business growth. This study investigates literature from various scholarly journals, including Jurnal Widya Ganecwara, Jurnal Publik, Jurnal Economina, Jurnal Ekonomi Efektif, Jurnal Pengabdian Kepada Masyarakat Tunas Membangun, and Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT). The main obstacles include technological limitations, a lack of competent human resources, legal uncertainties, and a high level of competition. The findings are expected to help business practitioners, policymakers, and academics develop innovative strategies to promote sustainable digital business growth in Indonesia.